(untitled) (Communication & Society, 2019)
This article focuses on otherness in the field of communications studies, within the social context of generalized mediatization. We argue that, on one hand, the new organizational dimension of communication, mediatization, based on information hybridism (Sodré, 2014), turns communication into a form of knowledge that is decisive for societal functioning. Yet, on the other hand, insofar as it integrates communication within information regimes –in particular, speed flows– mediatization seems to challenge the constitution of epistemological otherness within this field of knowledge. As a space in which synergy among different social fields is created, mediatization not only amplifies the discursive contiguity of knowledge-production and professional spheres, but also establishes the absence of duration as a common institutional premise. This phenomenon points to the retreat of time as a space of difference. Within the new regime of temporality, based on the virtual acceleration of time, a significant portion of communication theories seem to appear without any type of virtuality. In epistemological terms, one of the most acute consequences of dismantling time, as a space of intelligibility, is the constriction of the principle of autonomy that, at one time, more thoroughly grounded different fields of knowledge, especially within the humanities. Hence, the hermeneutic horizon becomes crucial to the development of social sciences. As a residual condition of discursive autonomy, hermeneutic resources shape an alignment of time and knowledge. In the end, understanding continues to constitute an existential quality